Knowledge, attitude and mis-conceptions regarding copper-T among women and ASHA workers in Bundelkhand region - Pandey, Piyush Kant; Shukla, Manu; Yadav, Pooja; Rai, Garima; Meena, Preeti; Mishra, Sneh; Rawat, Shivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Population explosion is probably the most challenging issue India is facing currently. According to the factsheet of National Family Health survey -5 (NFHS-5), the total unmet need for family planning methods in currently married women aged 15-49 years is 9.4% and the total unmet need for spacing methods is 4.0%. Also, IUCDs hold 2.1% of total share of contraceptives being used. Methods: 200 women coming to the hospital and 100 ASHA workers of Bundelkhand region accompanying them were included in this survey. They were asked to fill a questionnaire and results were analysed. Results: 56% of women knew about Copper-T as a contraceptive and only 25.5% women perceived it as an effective contraceptive. Theyraised concerns like bleeding, pain, infection and infertility. 53% ASHA workers reported women have only partial knowledge about Copper T. Conclusion: Copper T has low acceptance among women due to misconceptions and lack of awareness. Counselling, providing incentives to women, involving men and family members can improve its acceptance.